Pemberdayaan kelompok remaja berbasis budaya santri dalam optimalisasi peningkatan keterampilan kesehatan reproduksi remaja - Kustin Kustin; Zidni Nuris Yuhbaba; Nafisah Isnawati (INDRA: Jurnal Pengabdian kepada Masyarakat, 2023)
Adolescence is one of the stages in human life. This stage is a crisis stage because it is a transitional stage from childhood to adulthood. According to the characteristics of their sexual development, adolescents generally have developed sexual behavior in the form of heterosexual relationships or dating. The way to minimize reproductive health problems in adolescents, juvenile delinquency and drug abuse is to directly involve the community in. These Adolescents need increased skills to overcome problems that occur in adolescents, especially reproductive health problems. The purpose of this service is to form youth groups that are active in efforts to deal with existing reproductive health problems. This program is carried out from the perspective of human or community development through empowerment. The empowerment method is carried out by referring to the existing strategy. Existing strategies refer to and are based on the culture that exists in Islamic boarding schools or junior high schools in an effort to optimize their reproductive health skills. This activity was carried out in a youth group of 30 teenagers who were students and students at the Miftahul Ulum Kalisat Jember Middle School. Activities carried out for 3 months to assist empowered groups. The results of forming groups with this empowerment found that there was an increase in the skills possessed by adolescents related to reproductive health problems before the empowerment group was formed, the skills were not good by 65%, it decreased after the empowerment group was formed, it became 28%, while good skills, by 35%, it increased to 72%. It is hoped that the group that has been formed can continue the empowerment efforts based on the pesantren culture by optimizing reproductive health skills so as to make teenagers more innovative, creative and also active.health skills so as to make teenagers more innovative, creative and also active.